PENGGUNAAN METODE PEMBIASAAN BERKATA TOLONG, MAAF, TERIMA KASIH, DAN PERMISI DALAM MEMBENTUK AKHLAK ANAK - Ida Nurhayati; Yusuf Hidayat; Anggi Purwa Nugraha (Jurnal Intisabi, 2026)
This study was motivated by the suboptimal moral development in early childhood, characterized by a lack of polite behavior in daily interactions. The study aimed to determine the initial condition of the moral behavior of children aged 5-6 years at PAUD Sartika Asih prior to the intervention. Furthermore, the study examined the implementation and impact of the habituation method—specifically the consistent use of the words “please,” “sorry,” “thank you,” and “excuse me”—on their moral development. This Classroom Action Research (CAR) was conducted in two cycles, utilizing observation, interviews, and documentation as data collection techniques. Preliminary observation results indicated a low baseline mastery level for moral development, standing at only 34%. Following the implementation of the Cycle I intervention, the early childhoods’ moral mastery level increased to 62%. The integration of audiovisual media, involving singing and rhythmic clapping activities in Cycle II, significantly supported the mastery level to 85%. Interviews with parents further confirmed that the early childhoods had begun to spontaneously practice these manners in their home environment. In conclusion, the implementation of the “four magic words” habituation method proved highly effective in shaping and enhancing positive moral behavior in early childhoods.